A variant of a quasi-standard: attitudes of the young generation representing the Aukštaitian area - Kardelytė-Grinevičienė, Daiva (Lietuvių kalba, 2018)
he object of this paper is the variant of quasi-standard language, i.e. the variant of the perceived standard language formed by the young generation of the Aukštaitian area. The aims of the study are to examine whether the assessments made by respondents representing the Aukštaitian area suggest the presence of such a quasi-standard and, if they do, to provide the characterisation of this quasi-standard variant on the basis of the collected data. The data of the study consists of eight audio texts-stimuli which represent six Lithuanian regiolects (A and D represent Southern Aukštaitian; B and E represent Žemaitian, C represents Northwestern Aukštaitian, F represents the western part of Eastern Aukštaitian, G represents Southwestern Aukštaitian, while H represents the eastern part of East Aukštaitian) and the responses to two questions in the questionnaire designed according to the principles of perceptual dialectology which ask the respondents to rate the similarity of the audio text-stimulus to the standard language. The study demonstrated that the respondents perceived texts-stimuli B and E (representative of the Žemaitian dialect) as the least similar to the standard language. Texts-stimuli H (representative of the eastern part of East Aukštaitian regiolect), A and D (representative of East Aukštaitian regiolect), on the contrary, were seen as the closest to the standard language. Since the ratings of these texts-stimuli in the respondents’ assessment were substantially higher in comparison to the rest of the texts-stimuli, the results suggest the existence of a quasi-standard. The analysis of respondents’ motives of giving high scores to audio texts-stimuli A, D, and H demonstrates that the morphological and lexical characterisation of the quasi-standard of the young generation representing the Aukštaitian area is only fragmentary. The most prominent are phonetic features, namely: more open and more closed pronunciation of vowels i and u, shortening of unstressed long vowels o, u, and i, lengthening of the stressed short vowels u and i, correct accentuation and non-reduced endings. Based on the analysis carried out, it is possible to assume that the quasi-standard variety formed by the young generation representing the Aukštaitian area consists of some tertiary phonetic features of the eastern parts of East Aukštaitian and South Aukštaitian regiolectal zones, norms of standard language pronunciation, shortened verb forms typically characteristic of dialects and standard language and mixed lexis (containing that of standard language / dialects / borrowings).
Keywords: quasi-standard; young generation; Aukstaitian